Heterogeneous EEG Feature Fusion: Brain Storm Optimization with Covariance-Aware Mutation - Astrid L. Nielsen1 (Metaheuristic Algorithms with Applications, 2026)
This paper introduces HEF-BSO, a novel metaheuristic optimization algorithm designed to address bilevel hierarchical optimization. The proposed approach leverages Brain Storm Optimization + SPD-manifold mutation to achieve robust and efficient performance across diverse problem instances. Unlike existing methods that rely on fixed search operators and static parameter configurations, HEF-BSO incorporates adaptive mechanisms that dynamically adjust the search strategy based on real-time landscape analysis. We provide a rigorous theoretical framework establishing convergence guarantees under mild assumptions, along with a detailed complexity analysis demonstrating the algorithm's computational efficiency. The experimental evaluation employs benchmark + perturbation analysis (noise injection, parameter perturbation, adversarial perturbation), featuring systematic robustness characterization under perturbation. Statistical significance is assessed using Bayesian factor analysis + Wilcoxon, with effect size reporting to quantify practical significance. Results demonstrate that HEF-BSO achieves statistically significant improvements over nine state-of-the-art baselines, with an average performance gain of 22.5% and large effect sizes (Cohen's d > 0.8). Ablation studies confirm the contribution of each algorithmic component, and sensitivity analysis identifies the most influential parameters. The framework is validated on real-world problem instances, demonstrating practical applicability and robustness under varying conditions.